Two new species of Bothriocephalus Rudolphi, 1808 (Cestoda: Bothriocephalidea) from marine fish off Australia and New Caledonia - Kuchta, Roman; Scholz, Tomás; Justine, Jean-Lou (Systematic parasitology, 2009)
Two new species of bothriocephalidean tapeworms, Bothriocephalus australis n. sp. from the flatheads Platycephalus bassensis Cuvier (type host) and P. aurimaculatus Knapp off southern Australia and B. celineae n. sp. from a hybrid serranid Cephalopholis aurantia (Val.) x C. spiloparaea (Val.) from off New Caledonia, are described. B. australis is unique in the possession of the combination of the three characters: an elongate, obliquely situated cirrus-sac; a wide genital atrium surrounded by chromophilic cells; and a well-developed apical disc. B. celineae is typified by the presence of a low number of testes per segment (14-26), forming one or two incomplete longitudinal bands on each side of segment, and the small size of the strobila (total length 24 mm) which consists of less than 100 segments.
Keywords: Cestoda; Nová Kaledonie; Bass; Austrálie; Male; Animals; Percoidea; Australia; Chordata; mužské pohlaví; New Caledonia; Testis; zvířata; testis